Simulation of Consolidated Power System Behaviour in Steady and Self-Steady Modes - A. A. Zalatoi (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A complex mathematical model of behaviour of consolidated power systems with strong and weak internal intersystem electrical links in steady and self-steady modes is offered in view of automatic control of frequency, voltage and power. The model takes into account change of parameters of the circuit diagram according to frequency deviations and allows to simulate processes of frequency and power regulation in power system, direct current inserts, technical limitations and load effect.